Decolonizing childhoods : from exclusion to dignity - Liebel, Manfred, 1940- (Policy Press, 2020)
Uses a wide range of international case studies form the Global South to examine the stark repercussions of colonial conquest on children's lives and childhood policy today. Liebel shows the work that we must do to decolonize childhoods globally and ensure that children's rights are better promoted and protected.